Permeabilidade intestinal, translocação bacteriana e ocorrência de osteomielite vertebral em frangos submetidos ao estresse entérico - Rodrigues, Denise Russi (2018)
Vertebral osteomyelitis is an emerging disease in the world poultry industry, characterized by immobility and mortality of broilers and breeders chicken due to the infectious process in the fourth thoracic vertebra (T4). The aim of this study was to develop an experimental model induced by enteric stress to better understand the pathogenesis of vertebral osteomyelitis, as well as to investigate the role of enteric stress in intestinal permeability and bacterial translocation to liver, spleen and vertebral column of broiler chickens. Enterococcus cecorum strains (11 TXs and 11 TXb) that presented the virulence genes virulence factors: capsular polysaccharide I and II, enterococcal polysaccharide antigen M and P, protein lipoate synthase and surface protein LPTXG3 were inoculated after enteric stress induced by the use of dexamethasone for seven days in the diet (DEX), dried distilled grain with solubles - DDGS (30%) in the diet and the 24-hour food restriction (RA). The macroscopic findings of lesions responsible for claudication affected 19.37% (186/960) of the birds submitted to enteric stress and 9.06% (87/960) had vertebral osteomyelitis. The group that presented enteric inflammation induced by DDGS in the diet had an increase (p<0.05) in the incidence of vertebral osteomyelitis and lameness. The intestinal permeability, as assessed by serum FITC-d levels, increased (p<0.05) in DEX at 16, 23 e 30 days of age and RA at 30 days of age. After inoculation of E. cecorum, there was an increase (p<0.05) in microaerophilic bacteria in the liver and spleen in the DEX group at 20 days. Likewise, an increase of these bacteria was observed in T4 in the RA group at 27 days of age and in the DEX group at 34 days. Bacterial isolation identified a diversity of bacteria as species of Enterococcus, Streptococcus, Staphylococcus, Lactobacillus, as well as Escherichia coli in T4, suggesting that other microbial agents besides E. cecorum may be involved in vertebral osteomyelitis lesions. Therefore, the experimental reproduction model of vertebral osteomyelitis induced by enteric stress in broilers makes it possible to study vertebral osteomyelitis lesions, which favors its use in the applied research of preventive and therapeutic strategies for this disease. In addition, it is concluded that enteric stress increases intestinal permeability and promotes the translocation of opportunistic bacteria to the liver, spleen and spine of broiler chickens, which may lead to the development of vertebral osteomyelitis in broilers.